Identifikasi Jenis - Jenis Anggrek Epifit Di Kawasan Cagar Alam Mutis Timau, Kecamatan Tobu, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Maria Prischilla Christy Daton; Mamie E. Pellondo'u; Astin E. Mau (Wana Lestari, 2024)
This research was conducted in Mutis Timau Nature Reserve, Tutem Village and Tune Village in September 2023. This research used purposive method. Purposive side based on the height of the place where orchid plants exist. Qualitative data processing is used to obtain the name of orchid species. Samples of orchid species obtained are then processed and analyzed in accordance with orchid data that have key identification characters such as flowers, leaves, roots, stems and fruit. Composition of orchid species in Mutis Timau Nature Reserve Area as many as 18 species of epiphytic orchids Dendrobium sagitatum, Dendrobium purpureum, Dendrobium tetreadre, Ceologyne speciosa, Pholidota carnea, Vanda Limbata, Thrixpermum subulatum, Trichoglottis sp, Oberonia obesa, Luisia unguiculata, Bryobium retusum, Bulbophyllum sp 1, Bulbophyllum sp 2, Bulbophyllum odoratum, Ceratostyllis radiata Eria multiflora, Eria retusa, Flickingeria grandiflora.